PERANCANGAN DEFENSE SCHEME SISTEM INTERKONEKSI SULAWESI DENGAN MEMPERTIMBANGKAN KESEIMBANGAN DAYA - Pratama, Anugrah
Load shedding is a prevalent emergency control designed to prevent system blackouts. In power system operation, frequency issues occur because of the power imbalance between generation and load. If the generation is lower than load, system frequency will drop, conversely if generated power is higher than load frequency will rise. When generation deficiency is too large, system frequency will decrease significantly and can lead to system blackout. To solve this frequency issue, proper load shedding and islanding scheme is essential to prevent further deviation of system frequency from its nominal value In this research, a new defense scheme which consists of load shedding and islanding scheme is designed by considering active power balance. The defense scheme is designed for Sulawesi Interconnection System that consists of three systems: Southern Sulawesi (Sulbagsel), Southeast Sulawesi (Sulteng), and Central Sulawesi (Sulteng). The proposed scheme is simulated using DIgSILENT PowerFactory power simulation software, the obtained result then compared with the existing defense scheme for the same cases of disturbance. The goal is to render the design of a defense scheme that more systematic and effective with less load to be shedded.